Calidad de agua para consumo humano de la comunidad de Nina Rumi, San Juan Bautista, Loreto, 2024 - Sima Pacaya, Milca (2024)
The present work determined the microbiological quality of water for human consumption in the community of Nina Rumi -San Juan Bautista-Loreto, through by the most probable number (NMP) of fecal coliforms, Escherichia coli, plate count of aerobic mesophiles and biochemical identification of bacteria; as well as evaluate physical-chemical parameters such as turbidity, conductivity and pH. Two water samples were taken for human consumption directly from the taps that supply the community with safety and hygiene, identification and transportation protocols. Through the multiple fermentation tube technique, which is a quantitative method to assess the concentration of bacteria present in the water by inoculating a series of tubes in decreasing decimal concentrations of the sample, in a suitable culture medium, the which are incubated under conditions of time and temperature, then the incubation was carried out at 37°C x 48 hours, finding that there was no gas formation in any tube that could determine the growth or contamination of coliform bacteria. This final result, in addition to the organoleptic test previously developed, indicates that the water analyzed is suitable for human consumption as there is no evidence of growth of coliform bacteria through the technique used. We finally conclude that the water extracted from the wells is suitable for community consumption, showing that the septic wells are distant from the water collection points, also that their depth guarantees obtaining a good quality resource for its residents.